عصر حاضر میں وحدتِ امت کے لیے آں جناب ﷺ کے داخلی و خارجی معاہدات سے رہنمائیGuidance for the Unity of Ummah in Modern times through the Internal and External Treaties of the Prophet (Al-Qamar, 2021)
This paper will investigate how the Prophet (PBUH) used to make Internal and external agreements with the Muslims in his time and how can today Muslims, guided by these agreements, make the country a haven of peace? All these things will be explained in this study. Islam is a religion that promotes peace harmony and security at the national and international levels. For this purpose, Islam has laid down the principles of treaties and their observance which will be explained in this article. The aim of this article is to persuade the government to enter into agreements at the international level which do not harm the peace of the country. The all agreements of the Prophet (PBUH) are a guide line of all the human beings. The Holy Prophet (PBUH) made numerous agreements to create diplomatic state and good neighborly relations with neighboring tribes and countries of the Islamic state. For example He integrated the Jews and Muslims into collective unity through Medina peace agreement. The Prophet (PBUH) accomplished the peace task and achieved the results which no war could have happened. There is no better proof that this agreement of the repudiation of war as an instrument of policy and of his honest love of peace. The methodology of this research paper is descriptive and an analytic.
Keywords: Guidance; Prophet; Treaties; Unity of Ummah